Synthesis of degradable homopolymer, gradient and block copolymers, and self-assembly via RAFT polymerization of 4,4-Dimethyl-2-methylene-1,3-dioxolan-5-one - Er, Gerald Tze Kwang (2025)
Reversible addition-fragmentation chain transfer polymerizations of 4,4-dimethyl-2-methylene-1,3-dioxolan-5-one (DMDL) were conducted to yield degradable polymers with low dispersities. As well as homopolymers, random copolymers and block copolymers were synthesized by combining DMDL with various hydrophobic and hydrophilic monomers such as (functional) methacrylates, acrylates, and acrylamides, which are the so-called “more activated” monomers, and vinyl acetate and vinylpyrrolidone, which are the so-called “less activated” monomers. The obtained polymers were demonstrated to degrade under basic conditions. In the studied systems, random polymerization tended to yield gradient copolymers shifting from comonomer-rich segments to DMDL-rich segments, owing to the largely different reactivities of DMDL and comonomers. Such gradient copolymers may exhibit properties similar to those of block copolymers. Gradient copolymers with hydrophilic vinylpyrrolidone segments and hydrophobic DMDL-rich segments were synthesized and used to generate self-assemblies, i.e., micelles and vesicles, in water. The generated self-assemblies were demonstrated to degrade under basic conditions.